Scientific truth, power and obedience - Cárcamo Quezada, César (Acta Bioethica, 2011)
Physicians belief in objectivity without parenthesis, which assumes, in one side, the real existence of scientific truth and, in the other, confers the possibility of knowing such truth leaving aside subjectivity, which determines that certain physician-patient relations are of power and obedience, in which obedience is justified by promises of means and results, promises based in the belief of having access to an objective truth independent from actions taken. Based in the theory of knowledge of Humberto Maturana, we question this paradigm and, under biological insight, we propose a new look to objective knowledge.